Pengaruh Reliability, Responsiveness, Assurance, Empathy dan Tangibles Terhadap Kepuasan Konsumen GrabBike - Lusiana Lusiana; Salamun Pasda; Mustari Mustari; Muhammad Ihsan Said Ahmad; Muhammad Hasan (Universitas Negeri Makassar, 2020)
The purpose of this research are to see how reliability, responsiveness, assurance, empathy and tangibles affect the satisfaction of customer users of online transport services to UNM Economic students. Research conducted a method survey with quantitative approach. The population in this research is all students using grab bike online transport, ranging from 2016-2019 to 206 people. Sampling samples using technical samples of random sampling are 67 people. The instruments used to collect data are instruments of questionnaire, observation, and documentation. The data analysis technique used are regression analysis and hypothetical testing with T and F. data processing used SPSS version 21 for windows software. Research results show that variable as reliability, responsiveness, assurance, empathy, and tangibles are partial to positive and significant effects on users GrabBike online transport satisfaction. Simultaneously there is a positive and significant influence between reliability variables, responsiveness, assurance, empathy and tangibles to the consumer satisfaction users of GrabBike online transport services